ANALISIS WAKAF UANG DAN IMPLEMENTASINYA DI INDONESIA - Ahmad Ulil Albab Al Umar; Hikmah Endraswati; Yeyen Novita; Anava Salsa Nur Savitri (JURNAL ILMIAH EDUNOMIKA, 2022)
Cash waqf has become a new trend in waqf recently. Cash waqf itself can be done by anyone without a minimum limit on the amount of money in waqf right. This study aims to determine the concept, as well as views on cash waqf in Indonesia. The method used is descriptive analysis with a qualitative approach. The data in this study were obtained from secondary data sourced from journal articles, books, and other data. The results of this study indicate that cash waqf is currently a trend in society for waqf. The convenience and many choices provided by waqf institutions make it attractive and easier for waqifs who want to be waqf. According to the majority of scholars, cash waqf itself is permissible according to Islam. The implications of cash waqf can be expected as a new breakthrough for waqif who want waqf easily, then cash waqf itself is expected to overcome poverty and encourage the economy in Indonesia.